Wild eyes - Elsie Silver (London Piatkus, 2024)
FROM THE SUNSHINE SILVER! SET IN THE SAME BELOVED UNIVERSE AS SMASH-HIT SERIES CHESTNUT SPRINGS: SMALL-TOWN, BIG CHARACTERS, FOUR ADDICTIVE LOVE STORIES . . . MEET THE SINGLE DADS OF ROSE HILL. 'Elsie Silver's writing is a true revelation!' ALI HAZEL WOOD 'This book contains a hero to die for' TESSA BAILEY ---- A rugged mountain town seemed like the perfect escape from a life in shambles. But on day one, she ran full tilt into the world's hottest single dad, and now all her plans are ruined. As a chart-topping country singer with a recent streak of bad press, it's hard for Skylar Stone to find any peace. But she finds it in Rose Hill. With a little boy and a little girl who steal her heart just as thoroughly as their dad. Weston Belmont. The man is a shameless flirt. He oozes confidence and masculinity in a way that's downright distracting. And in bed? He's addictive. Everything with him is wild and impulsive, and Skylar is desperate to regain some control. But no one has supported her like West does. And no one has ever made her feel as loved as he does either. So, while Skylar's brain says settling down with a small-town horse trainer is impossible...her heart says she's right where she belongs. Still, her life as a celebrity haunts her. It has the power to pull she and West apart. She can see in his eyes that he wants her to stay. And she wants that too. But she knows better than anyone that you don't always get what you want. Readers can't get enough of the Rose Hill series . . . 'Billionaire romance but make it rustic . . . Elsie Silver just hits the mark every time' ? ? ? ? ? 'Hands-down my favorite book Elsie has written. HIGHLY recommend' ? ? ? ? ? 'Did I devour this in a single day? You bet I did!' ? ? ? ? ? 'Elsie Silver is the queen of small-town romances' ? ? ? ? ? 'The banter. The tension. The relationship between Ford & Rosie. The character development. Wow' ? ? ? ? ? 'I was hooked from the first chapter' ? ? ? ? ? *Wild Love was an instant Sunday Times bestseller in the second week of April 2024. Wild Eyes was an instant Sunday Times bestseller in the second week of September 2024.
Keywords: English Fiction